The Effect of Blended Learning and Student Learning Styles on Student Learning Outcomes - Dwi Yuliati; Atiqoh Atiqoh; Yoso Wiyarno (Journal on Education, 2023)
This study aims to determine and describe (1) the effect of learning outcomes using Blended learning and non-Blended learning on grade 3 students, (2) the effect of student learning outcomes using the V-A-K learning style on grade 3 students, and (3) the effect of interaction between learning Blended learning and learning styles on student learning outcomes in grade 3 SDN 1 Tanjungkalang Kec. Ngronggot Kab. Nganjuk. This study used an experimental design with a population and research sample of 3rd grade students at SDN 1 Tanjungkalang Kec. Ngronggot Kab. Nganjuk. Data collection techniques through questionnaires and tests as well as data analysis techniques using two-way analysis of variance. The calculation results obtained FA value (learning) = 7.010 with a significance value smaller than α <0.05, namely 0.011, meaning that there are differences in grade 3 student learning outcomes between those taught using blended learning and non-blended learning; FB value (Learning style) = 12.926, has a significance less than α <0.05, namely 0.000, meaning Fcount > Ftable, meaning that there are differences in grade 3 student learning outcomes between students who have visual, auditory and kinesthetic learning styles; and FAB scores (factors A and B) obtained an Fcount of 3.250 with a significant level of 0.038, so that there is an effect of using blended learning and non-blended learning models on student learning outcomes in terms of different student learning styles at SDN 1 Tanjungkalang Kec. Ngronggot Kab. Nganjuk.